State Capital Relocation and National Rice Field Prospects: Indonesian Agricultural Politics in an Era of Disruptive Innovation - Hasan Mustapa; Nanang Zulkarnaen; Mohammad Hadi Asykur Baraka (Politicon : Jurnal Ilmu Politik, 2022)
For Indonesia, relocating the national capital is one option for improving food security. Although, statistically, the ministry of agriculture's flagship program appears to have succeeded in increasing exports. Budget policies are actually shrinking in the field, and agricultural land is eroding. In addition, the state continues to import a number of strategic commodities such as rice and soybeans. The challenges of the innovation disruption era must be met with optimism. This paper seeks to understand how Indonesian agricultural politics can adapt to the era of disruptive innovation. The results of the analysis, conducted using a qualitative approach, show that: (a) the country's agricultural politics have so far been unable to produce new players capable of competing with the old players (incumbents), (b) the national agricultural strategy has not been able to present companies and entrepreneurs with disruptive innovation capabilities, (c) agricultural industry policy innovation is still limited, so it cannot promise lower margins and profits. Finally, the relocation of the capital city must be followed by the creation of creative paddy fields and an effective agricultural budget allocation strategy. A favorable ecosystem must be created to encourage the development of new competitive companies and new millennial farmers who are ready to face the Industrial Revolution 4.0. The private sector must also be involved in order to balance the government's and banks' suboptimal roles.